CURRENT DRUGS AND NEW THERAPEUTIC APPROACHES FOR THE LEISHMANIASIS TREATMENT - Costa, Monica Soares; Silva Nunes, Débora Cristina de Oliveira; Yoneyama, Kelly Aparecida Geraldo (Acta Biologica Brasiliensia, 2019)
Leishmaniasis is an endemic disease in 98 countries and 5 continents and approximately 1.3 million new cases occur annually. This work describes the main therapies used to treat the diverse clinical manifestations of leishmaniasis. Considering that the currently available anti-Leishmania drugs present several problems such as severe side effects and the possibility of parasitic resistance to the drug, among others, there is a constant search for new therapies for this disease. In addition to the drugs commonly used for the treatment of leishmaniasis, therapeutic alternatives such as metallic complexes were highlighted.